Correlation between High Carbohydrate Foods with Glycemic Index - Afandi, Frendy Ahmad (Perum BULOG, 2019)
High carbohydrate food has been perceived as a food with high glycemic index (GI). Meanwhile, the risks of diabetes are frequently associated with the GI carbohydrate based foods. Therefore, a comprehensive study based on the literature review regarding the relationship between high-carbohydrate food and the glycemic index needs to be conducted. High-carbohydrate foods can be grouped into the available carbohydrates type and non-available carbohydrates type. Food with available carbohydrates such as glucose, disaccharide, digestible oligosaccharides, and starch have positive correlation with the GI. The non-available forms of carbohydrates are hardly digested by the body, so they usually have low GI. The non-available carbohydrates foods are fructooligosaccharide (FOS) and galactooligosaccharide (GOS), raffinose, stachyose, and verbascose. High-carbohydrate foods can have low GI value due to complex carbohydrates or resistant starches. The type of carbohydrate can be turned into non-available due to chemical modification, processing, or interacting with other components. This information is necessary because recently, people have high awareness in choosing carbohydrate food. Not only the amount consumed, but also its carbohydrate content, types of carbohydrates, and how they are processed are important to be observed.